BEBERAPA SIFAT FISIS DAN KIMIA MINYAK BIJI SAGA LAUT (ADENANTHERA PAVONINA) - Gustan Pari; M Syachri (Jurnal Penelitian Hasil Hutan, 1989)
The  result  of  a study   on some  physical  and chemical  properties  of saga laut seed oil prepared  using pressing  method is presented   in this  report.The  result  shows   that  the  average  value  of  moisture   content,'  boiling  point,  specific  gravity,  iodine  number,   acid number   and saponification    value  respectively   are 0,137  percent,   166, 7 degrees celcius,  0,939,   31.04,   10,33  and  166, 72. Properties  of saga laut  seed  oil appear  to  be close  to  tengkawang  oil.